Correlation between Personal Hygiene, Household Hygiene, and Atopic Dermatitis in Elementary School Children in Indonesia (Majalah Kedokteran Bandung, 2020)
Atopic dermatitis is a chronic inflammatory skin disease characterized by persistent itching and reddening of the skin. In general, infants and children are more susceptible to atopic dermatitis. Many factors are associated with atopic dermatitis, one of which is personal hygiene. Personal hygiene is a condition or practice to maintain or improve personal health by keeping the body and the environment clean. Personal hygiene can influence the surrounding environment, such as by influencing the household hygiene. The purpose of this study was to determine the correlation between personal hygiene, household hygiene, and atopic dermatitis incidence among children who attended Pertiwi Elementary School Medan. This was a cross-sectional study with correlational analysis designed conducted at Pertiwi Elementary School Medan from July to December 2019. Data were collected using a questionnaire and analyzed using the Chi-Square test with p = 0.05 considered significant. Results showed that 28 children (39.4%) had atopic dermatitis, with more girls affected than boys (n=19, 67.9% vs. n=9, 32.1%). The overall household hygiene and cleanliness were good. There is a significant relationship between personal hygiene, household cleanliness, and the incidence of atopic dermatitis (p
Keywords: Atopic dermatitis; household hygiene; personal hygiene